2012
DOI: 10.1016/j.ydbio.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

In vivo knockdown of Brachyury results in skeletal defects and urorectal malformations resembling caudal regression syndrome

Abstract: The T-box transcription factor BRACHYURY (T) is a key regulator of mesoderm formation during early development. Complete loss of T has been shown to lead to embryonic lethality around E10.0. Here we characterize an inducible miRNA-based in vivo knockdown mouse model of T, termed KD3-T, which exhibits a hypomorphic phenotype. KD3-T embryos display axial skeletal defects caused by apoptosis of paraxial mesoderm, which is accompanied by urorectal malformations resembling the murine uro-recto-caudal syndrome and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 70 publications
9
33
0
Order By: Relevance
“…This fits the observation that murine T +/2 heterozygous embryos showed a 50% reduction of T-gene expression in the tail bud and notochord compared with wild-type mice (Pennimpede et al 2012). Pennimpede et al (2012) previously suggested that the T protein is directly involved in the maintenance of the mammalian seven cervical vertebrae blueprint because of the homeotic C7 . T1 transformation of cervical vertebrae in 30% of mice from in vivo T-gene knockdown experiments.…”
Section: T-gene Effects On Mammalian Blueprintsupporting
confidence: 88%
See 1 more Smart Citation
“…This fits the observation that murine T +/2 heterozygous embryos showed a 50% reduction of T-gene expression in the tail bud and notochord compared with wild-type mice (Pennimpede et al 2012). Pennimpede et al (2012) previously suggested that the T protein is directly involved in the maintenance of the mammalian seven cervical vertebrae blueprint because of the homeotic C7 . T1 transformation of cervical vertebrae in 30% of mice from in vivo T-gene knockdown experiments.…”
Section: T-gene Effects On Mammalian Blueprintsupporting
confidence: 88%
“…The murine brachyury (T) gene with its mutant alleles was the first gene that was identified and positionally cloned based on a genetic defect only, the long-known brachyury resulting in vertebral and spinal defects (Dobrovolskaia-Zavadskaia 1927;Herrmann et al 1990). Numerous subsequent studies confirmed that the coordinated expression of the T gene during gastrulation is essential for appropriate notochord, neural tube, and mesoderm development (Chesley 1935;Pennimpede et al 2012;Satoh et al 2012). Recently, the T gene has gained interest because of its association with the human chordoma, a sporadic and hereditary tumor originating from relicts of the notochord (Yang et al 2009;Pillay et al 2012;Nibu et al 2013).…”
mentioning
confidence: 99%
“…Our results indicate that notochord progenitors can also be diverted to neural fate in the absence of T function. Interestingly, ectopic neural structures were also observed in a previous report using a doxycycline-regulated T knockdown (14), but lack of lineage tracing and tissue restriction of the knockdown precluded establishing a definite causal relationship.…”
Section: T-knockdown Notochord Progenitors Survive But Adopt Neural Andmentioning
confidence: 74%
“…20 Antisense probes were generated by PCR from a total cDNA library from E10.5 where PCR products contained a 3 0 T7 RNA polymerase-binding site for in vitro transcription. Probes were purified using G-50 Sephadex columns (GE Healthcare, Munich, Germany).…”
Section: In Situ Hybridization Of Mouse Embryo Sectionsmentioning
confidence: 99%